IN RE OBSCURA VERSANTES. LA COMPLESSA QUESTIONE AGIOGRAFICA DEI MARTIRI AMITERNINI E NUOVE PROSPETTIVE DI INTERPRETAZIONE - Capannolo, Luca (Saeculum Christianum. Pismo Historyczne, 2017)
The story of eighty-three Martyrs of Amiternum has always left the few scholars which have approached it feeling frustrated and incomplete. The scant reliable data and the lack of studies in this regard have added to the mystery of a matter hagiographic already difficult to understand. This article doesn’t claim to solve this riddle, now consolidated and ingrained with the story of the martyrs, but want make an analysis of hagiographic material available and offer new perspectives of analysis based on the few secure facts in the history of Martyrs of Amiternum.